Sistem Informasi Coffee Shop Pada A Lot Of Coffee Berbasis Web - Alam, Syahirun; Rusdi, Rusdi (Jurnal Sintaks Logika, 2021)
Coffee is a drink that is brewed from coffee beans that have been roasted and ground into coffee grounds. In addition to the distinctive taste and aroma of coffee, it also contains caffeine which can help reduce the risk of developing cancer, diabetes, heart disease and various other diseases. Therefore, information related to coffee is created, apart from this application provides information about coffee, it also carries out the buying and selling process. The needs provided are several types of local coffee in the territory of Indonesia. Making this system using the PHP programming language. The system that is made has several features, namely the starting location of the delivery of goods in the pare-pare, the process of sending goods or orders is directly selected by the customer. The delivery services used are JNE, JTE and the Post Office. For goods purchase transactions, customers can choose the payment method available on the application, namely via transfer or using the OVO application that is already listed on the application.